Acute respiratory failure as presentation of late-onset Pompe disease complicating the diagnostic process as a labyrinth: a case report - Menzella, Francesco; Codeluppi, Luca; Lusuardi, Mirco; Galeone, Carla; Valzania, Franco; Facciolongo, Nicola (Multidisciplinary Respiratory Medicine, 2018)
Background: Acute respiratory failure can be triggered by several causes, either of pulmonary or extra-pulmonary origin. Pompe disease, or type II glycogen storage disease, is a serious and often fatal disorder, due to a pathological accumulation of glycogen caused by a defective activiy of acid α-glucosidase (acid maltase), a lysosomal enzyme involved in glycogen degradation. The prevalence of the disease is estimated between 1 in 40,000 to 1 in 300,000 subjects. Case presentation: This case report describes a difficult diagnosis of late-onset Pompe disease (LOPD) in a 52 year old Caucasian woman with acute respiratory failure requiring orotracheal intubation and subsequent tracheostomy for long-term mechanical ventilation 24 h/day. Despite a complex diagnostic process including several blood tests, bronchoscopy with BAL, chest CT, brain NMR, electromyographies, only a muscle biopsy allowed to reach the correct diagnosis. Discussion: The most frequent presentation of myopathies, including LOPD, is proximal limb muscle weakness. Respiratory related symptoms (dyspnea on effort, reduced physical capacity, recurrent infections, etc.) and respiratory failure are often evident in the later stages of the diseases, but they have been rarely described as the onset symptoms in LOPD. In our case, a third stage LOPD, the cooperation between pulmonologists and neurologists was crucial in reaching a correct diagnosis despite a very complex clinical scenario due to different confounding co-morbidities as potential causes of respiratory failure and an atypical presentation. In this patient, enzyme replacement therapy with infusion of alglucosidase alfa was associated with progressive reduction of ventilatory support to night hours, and recovery of autonomous walking.